2000
DOI: 10.1099/00221287-146-1-7
|View full text |Cite
|
Sign up to set email alerts
|

Use of green fluorescent protein (GFP) to study the invasion pathways of Edwardsiella tarda in in vivo and in vitro fish models

Abstract: Edwardsiella tarda is a fish pathogen that causes systemic infections in many food and ornamental fish. E. tarda PPD130/91 and PPD125/87 were selected as representatives of the virulent and avirulent groups, respectively, from eight fish isolates, and transformed with plasmids encoding either green fluorescent protein (pGFPuv) or blue fluorescent protein (pBFP2). Two host models were used to study the invasion pathway of E. tarda in vitro and in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
120
0
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(126 citation statements)
references
References 40 publications
3
120
0
3
Order By: Relevance
“…The bacterial strains and plasmids used in this study are described in Table 1. E. tarda PPD130/91 (22) and its derived strains were grown in tryptic soy broth (TSB; BD Biosciences) at 25°C and Escherichia coli strains in Luria-Bertani broth (LB; BD Biosciences) at 37°C. To induce the expression of T3SS proteins, E. tarda strains were grown at 25°C in Dulbecco modified Eagle medium (DMEM; Invitrogen) under 5% (vol/vol) CO 2 atmosphere.…”
Section: Methodsmentioning
confidence: 99%
“…The bacterial strains and plasmids used in this study are described in Table 1. E. tarda PPD130/91 (22) and its derived strains were grown in tryptic soy broth (TSB; BD Biosciences) at 25°C and Escherichia coli strains in Luria-Bertani broth (LB; BD Biosciences) at 37°C. To induce the expression of T3SS proteins, E. tarda strains were grown at 25°C in Dulbecco modified Eagle medium (DMEM; Invitrogen) under 5% (vol/vol) CO 2 atmosphere.…”
Section: Methodsmentioning
confidence: 99%
“…The pathogenesis of Ed. tarda is multifactorial, including factors that enable the bacteria to invade non-phagocytic cells (Kourany et al, 1977;Ling et al, 2000), survive in phagocytes (Srinivasa Rao et al, 2001, and produce virulence factors such as haemolysins (Janda & Abbott, 1993;Chen et al, 1996) and catalases (Srinivasa Rao et al, 2003). Recently, two important protein secretion systems, a type III secretion system (T3SS) (Tan et al, 2005;Zheng et al, 2007) and a type VI secretion system (T6SS) (Zheng & Leung, 2007), have been demonstrated to be virulence-associated.…”
Section: Introductionmentioning
confidence: 99%
“…It has been isolated from a variety of animals, including fish, birds, mammals, and reptiles (12,27,31,46,47), and environmental water (32,50). Several potential virulence properties have been suggested to contribute to the pathogenesis of E. tarda, namely, the production of dermatotoxin (45) and hemolysin (14) and the ability to resist phagocyte-mediated destruction and to invade epithelial cells (19,22,43). However, little is known about the pathogenic mechanism of E. tarda, and the causes of disease occurrence are still elusive.…”
mentioning
confidence: 99%